My holiday in USA - Brooks, Susie (London : Wayland, 2008)
Text and photographs provide an introduction to USA, discussing weather, sights, transportation, cuisine, daily life, and more.
Includes index.
4.1
3-6.
3-6
Keywords: United States -- Juvenile literature; United States -- Description and travel -- Juvenile literature; United States; United States -- Description and travel; United States. .; United States -- Description and travel